Enhancing crude oil emulsion separation: Investigating the influence of emulsion properties on microwave demulsification - Abdulqawi, Mohammed; Nur Najwa Syuhada, Suhaidi; Rahimah, Embong; Norasyikin, Ismail (AIP Publishing, 2025)
The emulsion issue in the production and refining of crude oil has garnered significant attention from oil companies and researchers in recent decades, both theoretically and practically. The stabilization of emulsions is attributed to the presence of an interfacial barrier that hinders the coalescence of dispersed water droplets. This barrier is formed by polar substances within crude oil, such as asphaltenes, resins, wax, and naphthenic acids. Consequently, it is imperative to separate water before the transportation or processing of oil due to economic and operational considerations. Mitigating water levels in oil serves to reduce corrosion and optimize pipeline utilization. Chemical demulsification using demulsifier additives can be very effective but requires optimization of demulsifier formulation and dosage for each emulsion. It also introduces added chemicals. Thermal treatment such as heating emulsions to reduce viscosity and encourage droplet coalescence is simple but energy intensive. Microwave heating is more rapid and selective, allowing lower overall energy usage. However, conventional heating can be applied continuously to large emulsion volumes. Microwave irradiation, a cost-effective and environmentally friendly heating technique, has exhibited favorable characteristics such as enhanced efficiency, reduced reaction times, and improved product yields. As a result, it has emerged as a highly effective approach for demulsifying crude oil. Microwave demulsification provides rapid, low-cost, and chemical-free emulsion breaking for batch treatment. It can complement conventional demulsification methods by providing a supplemental technique for certain emulsion types or as a polishing step to achieve final residual water specifications. Further development of continuous flow microwave systems could make this technology more competitive for large-scale demulsification applications. This research inspects the impact of crude oil emulsions, such as pH, salt concentration, and moisture level, on crude oil demulsification using microwave irradiation. A group of batches of demulsification experiments have been conducted using different parameters of salt concentration, water content, and acidity to determine the residual emulsion’s H2O content after being exposed to microwave radiation. Emulsions with high water content are anticipated to exhibit lower demulsification efficiencies in microwave processes. This study explores new methods that effectively separate water-in-oil emulsions within short timeframes. These procedures should also be cost-effective, easily implementable, and applicable to various scenarios without requiring time-consuming calibrations. The findings of this work revealed that the optimum demulsification efficiency is achieved at pH 7, 30,000 ppm salinity, and 45 % water content.